2020
DOI: 10.2147/rru.s261888
|View full text |Cite
|
Sign up to set email alerts
|

<p>Peri-Operative Factors Affecting Blood Transfusion Requirements During PCNL: A Retrospective Non-Randomized Study</p>

Abstract: Background Percutaneous nephrolithotomy (PCNL) is accepted as the gold standard of care for the treatment of large renal calculi. Kidney hemorrhage, which requires blood transfusion, is one of the most common complications after percutaneous kidney stone surgery. Objective To evaluate perioperative factors associated with transfusion requirements during PCNL. Materials and Methods A total of 226 patients with kidney calculi undergoing PCNL be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…Tis was probably due to less stone bulk in our study than in Elnagar et al [19] study, which was 34.2 ± 9.8 mm. It has been reported that the blood transfusion rate during PCNL is about 3.5%-9.29% [21,22]. Jain et al investigated prophylactic phenylephrine and ephedrine infusion during spinal anesthesia for an emergency cesarean.…”
Section: Discussionmentioning
confidence: 99%
“…Tis was probably due to less stone bulk in our study than in Elnagar et al [19] study, which was 34.2 ± 9.8 mm. It has been reported that the blood transfusion rate during PCNL is about 3.5%-9.29% [21,22]. Jain et al investigated prophylactic phenylephrine and ephedrine infusion during spinal anesthesia for an emergency cesarean.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the use of large equipment in pediatric kidneys may result in renal parenchymal destruction, a decline in glomerular filtration rate, and it may invoke major complications including sepsis, hydrothorax, septicemia, and kidney hemorrhage that may require blood transfusion. 6 , 7 Moreover, the major disadvantage of the prone position in PNS is presumably the complexities and difficulties with respiration management for the anesthesiologist. We decided to perform the procedure in the GMSV position to ensure safe access to the airway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the incidence of postoperative surgical complications can be associated with multiple variables, such as complexity of the procedure, patient characteristics, and the surgeon's case volume. [11][12][13][14] Scoring systems or nomograms were developed using the aforementioned variables in order to assess procedural complexity and predict outcomes, which helps with risk assessment for patient counseling, surgery 150 preparation, prediction of the postoperative phase, and standardized reporting of the outcome measures. Generally, a clinical scoring system should be easy to calculate and utilize rapidly, without significant training or specialized software.…”
Section: Discussionmentioning
confidence: 99%